Socio-demographic differences in the prevalence of cardiovascular diseases and the association with risk factors in the population of Serbia - Šašić Bojana M.; Čanković Dušan K.; Mijatović-Jovanović Vesna P.; Ukropina Snežana N.; Ostojić Zorana Z.; Milijašević Dragana S.; Stamenković Kristina D.; Čanković Sonja I. (Hospital Pharmacology)
Introduction: Cardiovascular diseases are the leading cause of mortality in the world. This study aimed to examine the prevalence of cardiovascular diseases in relation to socio-demographic characteristics, behavioral and metabolic risk factors, and to analyse the association between presence of cardiovascular diseases and self-perceived health and attitudes towards factors affecting health in the population of Serbia over the age of fifteen. Material and Methods: The data of the 2019 National Health Survey of the Population of Serbia were analyzed, on a sample of 13,178 respondents over the age of fifteen, which was conducted in accordance with the methodology of the European Health Interview Survey (Wave 3). Data on socio-demographic characteristics, metabolic and behavioral risk factors and self-reported health and factors influencing health in relation to cardiovascular diseases were used for our analysis. Testing the difference in frequencies of categorical variables was performed using the X 2 test. Values of significance level p<0.05 are considered statistically significant. Results: By analyzing the data obtained from this research, it was estimated that every ninth resident of Serbia (11.2%) suffers from some form of cardiovascular diseases, with a statistically significant difference observed in the prevalence of cardiovascular diseases in relation to gender, age, income, education, self-assessment of health and attitudes towards health and risk factors, except for physical activity. Conclusion: The high prevalence of cardiovascular diseases is strongly associated with preventable risk factors, such as obesity, hypertension, alcohol consumption, and smoking. This highlights the need for the development of preventive programs aimed at strengthening cardiovascular health education.